Flexural Performance of Direct Resin Composite Restorative Materials Past Expiration Date - Nagaoka, Hiroko; Bishop, Susan; Roberts, Howard (European Journal of Dentistry, 2020)
Objective This study' s purpose was to examine the flexural properties of five direct restorative resin composites stored up to 30 months after the expiration date.Materials and Methods Ambient-stored materials had pre-expiration date baseline flexure strength values as per ISO 4049 (n = 20). All materials were used per manufacturer guidelines, photopolymerized on both sides using a LED-based visible light curing unit, and stored in 0.2M phosphate buffered saline. At 24 hours, specimens were stressed to failure in three-point bend at a 0.5 mm/min cross head speed. Additional samples were made at 3, 6, 9, 12, 15, 18, 24, and 30 months past expiration date. Young’s modulus (flexural) was ascertained using the linear slope of the stress-stain curve.Statistical Analysis The mean data was found to contain a non-normal distribution and irregular variance which was compared using Kruskal–Wallis with Dunn’s posthoc testing.Also, Pearson’s correlation analysis was used to identify possible similar degradation behavior between products within both flexure strength and modulus determinations. A 95% level of confidence (α = 0.05) was used.Results Materials maintained similar to baseline flexure strength and modulus for up to 15 months past expiration date with two materials being similar at 30 months. However, clinicians were still advised to follow expiration dates, as resin composite degradation mechanisms are complex and vital constituents might degrade that are not overtly identified by clinical handling characteristics. No dental shelf life standards exist and manufacturers are requested to provide protocol information used in determining shelf life expiration.
Keywords: resin restoration; shelf life; expiration date